Effects of Neuromuscular Electrical Stimulation on Swallowing Functions in Children with Cerebral Palsy: A Pilot Randomised Controlled Trial - Woo Jin Song; Ji Hyuk Park; Joo Hyun Lee; Min Young Kim (SAGE Publishing, 2015)
Objective/Background: Oral-motor and sensory dysfunctions are primary reasons for difficulties with swallowing in children with cerebral palsy (CP). Neuromuscular electrical stimulation (NMES) has been shown to provide positive effects on the swallowing function in adult populations with various neurological disorders. However, there is a lack of studies regarding the effects of NMES in children with dysphagia. The aim of the present study was to investigate the effects of NMES and oral sensorimotor treatment (OST) by occupational therapists in children with CP and dysphagia. Methods: The present study was a two-group experimental design. Participants were randomly assigned to either the experimental group (n = 10) or the control group (n = 10). The NMES group received both NMES and OST, with NMES on the pharyngeal level for 20 minutes after OST, while the control group received OST and sham-NMES only. The treatment sessions occurred twice a week for 8 weeks. Results: The experimental group demonstrated a significant improvement in: lip closure while swallowing, ability to swallow food without excess loss, ability to sip liquid, ability to swallow liquid without excess loss, and ability to swallow without cough (p < .05). Conclusion: This study demonstrated that OST and NMES facilitated swallowing functions than OST and sham-NMES in children with CP and dysphagia. Future studies need to utilise video fluoroscopy swallowing study for outcome measurements in a large participant group.